The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fendo.2020.543623
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Mesenchymal Stem Cells Promote Endogenous Bone Regeneration

Abstract: Bone regeneration has become a research hotspot and therapeutic target in the field of bone and joint medicine. Stem cell-based therapy aims to promote endogenous regeneration and improves therapeutic effects and side-effects of traditional reconstruction of significant bone defects and disorders. Human amniotic mesenchymal stem cells (hAMSCs) are seed cells with superior paracrine functions on immune-regulation, anti-inflammation, and vascularized tissue regeneration. The present review summarized the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“… 19 Meanwhile, the amniotic membrane is an avascular structure only composed of epithelium and mesenchyme, which makes it easy to remove epithelial layer by Dispase II and thus obtain hAMSCs without contamination of endothelial cells and hematopoietic cells. 20 Our previous study found that the immunomodulatory and proliferation activity of hAMSCs is higher than that of human bone marrow MSCs in vitro. 21 , 22 Yamahara et al confirmed that human amnion-derived MSCs had immunomodulatory activity equal to or higher than that of human bone marrow MSCs.…”
Section: Introductionmentioning
confidence: 96%
“… 19 Meanwhile, the amniotic membrane is an avascular structure only composed of epithelium and mesenchyme, which makes it easy to remove epithelial layer by Dispase II and thus obtain hAMSCs without contamination of endothelial cells and hematopoietic cells. 20 Our previous study found that the immunomodulatory and proliferation activity of hAMSCs is higher than that of human bone marrow MSCs in vitro. 21 , 22 Yamahara et al confirmed that human amnion-derived MSCs had immunomodulatory activity equal to or higher than that of human bone marrow MSCs.…”
Section: Introductionmentioning
confidence: 96%
“…The amniotic membrane is a “discarded” tissue of particular interesting after parturition, which contains epithelial and mesenchymal stem cells with low immunogenicity, robust proliferation, multi-lineage differentiation capacity, and easy procurement [ 37 – 39 ]. Therefore, hAMSC-based therapy has been widely explored to promote endogenous regeneration and alleviate the untoward effect of traditional treatment [ 40 ]. To date, hAMSCs have been reported as appropriate sources with therapeutic effects in regenerative medicine and tissue engineering such as premature ovarian insufficiency (POI) [ 41 ], premature ovarian failure (POF) [ 36 ], wound healing and epithelialization [ 42 ], hepatocellular carcinoma [ 43 ], and endogenous bone regeneration [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hAMSC-based therapy has been widely explored to promote endogenous regeneration and alleviate the untoward effect of traditional treatment [ 40 ]. To date, hAMSCs have been reported as appropriate sources with therapeutic effects in regenerative medicine and tissue engineering such as premature ovarian insufficiency (POI) [ 41 ], premature ovarian failure (POF) [ 36 ], wound healing and epithelialization [ 42 ], hepatocellular carcinoma [ 43 ], and endogenous bone regeneration [ 40 ]. Generally, hAMSCs function via direct- and trans-differentiation, paracrine, and autocrine (e.g., extracellular proteins, anti-bacterial peptides, growth factors, angio-modulatory cytokines, bioactive factors), immunoregulation (e.g., anti-inflammatory agents, polarization of T lymphocytes, or macrophages), activating endogenous regeneration and serving as constitutive microenvironment [ 17 , 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These bodies of literature suggest that AECs and AFCs have the potential to effectively treat a variety of conditions, ranging from cutaneous wounds to orthopedic conditions, to liver or lung disorders, and neurological conditions. While some efficacy has been shown in certain clinical contexts [ 59 , 60 , 61 ], it is clear that these treatments are safe when properly administered [ 62 , 63 ]. Furthermore, the therapeutic effects appear to be mediated not necessarily by the cells directly, but by their secreted trophic factors [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%